Enhancing Co-Gasification of Coconut Shell by Reusing Char - Monir, Md Minhaj Uddin; Yousuf, Abu; Azrina, Abd Aziz; Atnaw, Samson M. (Informatics Publishing Limited, 2017)
Objectives: This paper aims to investigate the influence of char reuse in the gasification process. Methods: Co-gasification of biomass (coconut shell) and char was carried out in a downdraft gasifier. Char was produced as a by-product in biomass gasification process which contains a huge amount of concentrated carbon. The simulation was run for the different ratios of coconut shell and char (100:0, 90:10, 80:20 and 70:30) by ASPEN PLUS process simulator software to find out a suitable ratio. Findings: The calculated energy is 23703.45 Kcal, 24207.78 Kcal, 24964.28 Kcal and 25468.60 Kcal, where the char ratio is 0%, 10%, 20% and 30%, respectively. Based on the simulation result, gasification was accomplished by adding 30% of char with coconut shell biomass. The simulated and experiment results proved that more energy can be produced by increasing the char ratio. Application: Many countries started to find out an alternative source of energy instead of nonrenewable energy resources, especially from biomass. Co-gasification of the coconut shell with suitable char ratios is the best alternatives to meet up the world’s future energy demand.